Estimating Level Effects In Diffusion Of A New Technology: Barcode Scanning At The Checkout Counter - Jonathan Beck; Michał Grajek; Christian Wey (European School of Management and Technology (ESMT), 2007)
Cross-country or cross-industry studies of technology diffusion typically estimate how independent factors affect diffusion speed or timing, often based on a two-stage approach. In many applications, however, countries (industries) differ most in the saturation level of diffusion. In a novel, single-stage econometric approach to a standard diffusion model, we therefore estimate how the saturation level covaries with independent factors. In our application to diffusion of an important retail information technology, we focus on the competitive effect of hypermarkets (superstores). We also find standard scale, income and labor substitution effects.
urn:nbn:de:101:1-201106143406
Keywords: L5; L81; O33; 650; diffusion; information technology; retail competition